2020
DOI: 10.1038/s41598-020-68346-y
|View full text |Cite
|
Sign up to set email alerts
|

Different precipitation response over land and ocean to orbital and greenhouse gas forcing

Abstract: Various proxies suggest a nearly in-phase variation of monsoons with local summer insolation. Oceanic proxies of monsoons document a more complex response. Climate model simulations also indicate that the response is different over land and ocean. Here using a transient simulation by a climate model over the last 22,000 years we have unraveled the factors that lead to these differences within the Indian subcontinent. We show that during the deglacial (22–12 ka) precipitation over India and the Bay of Bengal (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Hence, idealized simulations indicate a 180° phase difference between the precession-band timing of maximum summer monsoon precipitation over the ocean versus the nearby continents. Jalihal et al (58,65) discuss the mechanisms underlying these simulation results. They find that precipitation over land is more sensitive to radiation forcing (net top of atmosphere long wave and short wave), whereas surface latent heat flux (dominated by winds) and vertical stability are more important over the BoB, again, keeping in mind that IV and GHG forcing are not included in these idealized simulations.…”
Section: Precession Phasementioning
confidence: 99%
“…Hence, idealized simulations indicate a 180° phase difference between the precession-band timing of maximum summer monsoon precipitation over the ocean versus the nearby continents. Jalihal et al (58,65) discuss the mechanisms underlying these simulation results. They find that precipitation over land is more sensitive to radiation forcing (net top of atmosphere long wave and short wave), whereas surface latent heat flux (dominated by winds) and vertical stability are more important over the BoB, again, keeping in mind that IV and GHG forcing are not included in these idealized simulations.…”
Section: Precession Phasementioning
confidence: 99%
“…Thus, indicating that the relationship between LLJ and the monsoon rainfall may be different in different climate regimes. This view is supported by recent studies where it was shown that it is the net energy flux into the atmosphere and water vapor, and not the monsoon winds that account for variability of South Asian monsoon on centennial and longer timescales (Jalihal, Srinivasan, et al., 2019; Jalihal et al., 2020).…”
Section: Introductionmentioning
confidence: 79%
“…In our previous work Jalihal et al, 2020), using the energetics of monsoons we have shown in the TraCE-21k that net energy flux into the atmosphere (Q div ) and total column water vapor (P wat ) are enough to explain the orbital scale variability of monsoons. Insolation drives fluctuations in monsoons primarily through Q div , whereas greenhouse gases and ice sheets affect the gross moist stability through their impact on P wat .…”
Section: Discussionmentioning
confidence: 99%
“…Source: Ministry of Environment, Forest and Climate Change, Government of India, 2018 [9] Because of global warming, more meteorological disasters happen which interpret the normal monsoon rainfall patterns. Based on Jalihal et al [10] investigations, maize and wheat yields are expected to decrease by two to five percent for every degree of temperature increase in India. Thus, the extra gain from increased temperature is not significant to compensate for the devastating loss of the expected yield reduction of the four major crops worldwide.…”
Section: Paris Agreement's Impact On Different Industries 31 Impact O...mentioning
confidence: 99%